Quantitative analyses of the umami characteristics of disodium succinate in aqueous solution. (30th June 2020) - Ma, Jie; Chen, Yanping; Zhu, Yiwen; Ayed, Charfedinne; Fan, Yuxia; Chen, Gaole; Liu, Yuan
Highlights: Disodium succinate (WSA) contributes to umami taste. WSA exhibits the strongest relative umami taste at the condition of 25 °C, 0.1% Na + addition, and pH 7.5. WSA shows good stability after heat treatment. Abstract: Disodium succinate (WSA) contributes to umami taste in seafoods and it is abundantly found in scallops. However, the actual application of WSA in foods is limited due to a lack of understanding of its taste characteristics and stability. In this study, two-alternative forced choice method was used to determine the relative umami intensity of WSA compared to monosodium glutamate, as well as the relative umami intensity under different conditions (pH and temperature). WSA concentration–taste intensity curve was established, which fitted well with a logarithmic-linear regression ( R 2  = 0.96). WSA exhibited the strongest umami intensity at 25 °C, 0.1% Na + addition, and pH 7.5. It also had a good thermal stability, which met the needs of high temperature heating during food processing. In conclusion, this research provided useful information on umami characteristics of WSA and the results widen the application of WSA in the food industry.